Solving The Fully Fuzzy Sylvester Matrix Equation With Triangular Fuzzy Number - Malkawi, Ghassan; Ahmad, Nazihah; Ibrahim, Haslinda (Pushpa Publishing House, 2015)
This paper proposes a new method for solving the fully fuzzy Sylvester matrix equation (FFSE). This method is considered as an extension of the solution for the positive fully fuzzy linear system (FFLS). The fully fuzzy matrix system is converted into an associated linear matrix system to obtain a crisp solution. This method is able to solve FFLS and left right - fuzzy linear system (LR-FLS). A numerical example is presented to demonstrate the contributions of this paper